Acquisition of wealth as a demonstration of belongingness in K.S. Maniam's selected works - Mani, Manimangai (2016)
Establishing sense of belongingness to a country is one of the most crucial issues for people who are displaced. The colonization of British over Asia and the rest of the world resulted in millions of people being displaced and scattered in countries which were once British colonies. One of the races that were displaced in large numbers is the Indians. The mass movement and the displacement of the Indians, especially the Tamils from South India to Malaya began in the middle of 19th century. Most of them were brought in to fulfil the labour needs in the rubber plantations from 1844 to 1941. At present, the Indians make the third largest ethnic group in Malaysia. Malaysia also has the largest number of Indians compared to any other country in the world, with 1.8 million people. This study will discuss the issue of displacement and the struggles of the immigrant Indians who came to Malaya looking for a greener pasture. At the same time, their descendents, who have now become citizens of the new country after the independence of Malaysia, will also be examined to see the impact of displacement in their lives. All these will be analyzed through K.S. Maniam’s novels, The Return (1981) and In a Far Country (1993). This study will also expose the struggle and the difficulties faced by these immigrant Indians and descendants. Finally, this study will show why acquisition of wealth became the main motive to these characters to establish a sense of belongingness to the country.